Assessing the impact of social media on farmers’ income: evidence from Punjab, Pakistan - Amir Hamza; Dai Yonghong; Ihsan Ullah; Nawab Khan (Frontiers in Sustainable Food Systems, 2025)
Increasing farmers’ income and ensuring food security remain significant challenges in Pakistan’s agricultural sector. Social media adoption offers new opportunities for knowledge sharing, market access, and productivity gains; however, its impact on agricultural income remains underexplored. This study investigates the impact of social media usage during the production stage on crop farmers’ income in Punjab, Pakistan, and explores the underlying mechanisms, including improvements in technical efficiency, land productivity, and agricultural labor efficiency. Using survey data from 480 crop farmers, an endogenous switching regression model is employed to estimate the causal effect of social media usage on agricultural income. Mediation analysis further examines how productivity improvements drive income growth. Social media usage significantly increases agricultural income, with results remaining robust across alternative estimation methods. These income gains are primarily driven by improved technical efficiency and land productivity. They are especially evident among farmers with higher education levels, larger landholdings, and greater initial income. These findings underscore the transformative role of social media in rural development by facilitating better access to information and improved farm performance. To amplify these benefits, policymakers should prioritize expanding digital infrastructure, promoting digital literacy, and improving access to agricultural information, particularly for smallholder and low-income farmers.